Water Flow through Veins in Ice - Colbeck,Samuel C. (1976)
Water flow through the vein structure of temperature ice is described as Darcian flow in which the pressure gradient is determined from vein size and overburden pressure. A solution method for the resulting equation is given and two special cases are considered. For steady flow the equilibrium vein size is a function of depth and, by neglecting the effects of diffusion, it is shown that flow perturbations introduced at the surface propagate downward at a constant speed. These perturbations propagate so slowly that even annual surface fluctuations of flow may be eliminated by diffusion before reaching the bottom of the glacier.